Company characteristics and corporate social responsibility disclosure of Malaysian listed companies - Rosli, Mohamad Hafiz; Fauzi, Nuruu Ain; Mohd Azami, Muhammad Fadhirul Anuar; Mohd, Farahwahida; Said, Jamaliah (2016)
Towards realizing Malaysia’s Vision 2020,Corporate Social Responsibility (CSR) has been viewed as an important part for a business to succeed.With the increasing awareness and global demand for better CSR practices, companies need recognize and adopt them into their management practices.However, in today’s emerging market, several factors could influence the adoption of CSR as part of their business strategy. This research aims to identify the focus level of Corporate Social Responsibility Disclosure (CSRD) in Malaysia Meanwhile, four identified factors such as company size, profitability, share return, and industry type were tested to the CSRD.Secondary data obtained from 100 public listed companies across industries were analysed and reported in this study. Constructed CSRD checklist was used to identify the focus level of CSRD, and multiple regression analysis was employed to test the relationships of the above stated variables.In conclusion, the highest and least disclosures were community and marketplace, respectively.The finding also indicates that company size, profitability and share return have significance relationships with the CSRD while the industry type was not significantly linked with CSRD.This finding could benefit the government and policy makers to consistently encourage corporates to practice CSR and to place appropriate emphasis awards for those who comply such as tax incentive, CSR awards; special rules exempted or granted government grants.Therefore, the corporations also need to move forward from just a voluntary disclosure to the betterment of nation sustainability.